Poe’s Perspective of Beauty as Reflected In “Ligeia” - Sumayah, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
The research was an attempt to “describe” Poe’s perspective of beauty reflected in “Ligeia”, a short story. This study used American Studies theory that was the reconciliation of time (past, present, future), of space and of academic discipline that were philosophical, historical, and literary approaches. The literary approach used, in this case, was the expressive one. The method applied in this study was analytical descriptive that utilized library research and concentrated the attention on reference sources related to the topic discussed. The result of the study showed that romantic ideas influenced the American society. The most striking ones were the freedom, individualism and equality. Individualism and freedom made Poe’s literary works that in a way can be categorized as classic and in another way, romantic. They were different from the others. This study proved that Poe’s perspective of beauty was that the well designed poem or prose creates the pleasure of totality of beauty. Beauty is the sole legitimate province of the poem. The beauty must be able to elevate soul. It can be found from the contemplation of the beautiful. The study also showed that “Ligeia” reflects the beauty of knowledge.